2018
DOI: 10.1186/s40248-018-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep quality with excessive daytime somnolence and quality of life of elderlies of community

Abstract: BackgroundThe progressive increase in the elderly population contributes to the fact that studies on human aging have important attention of health professionals and government agents, since they present a great challenge regarding public health. Our objective is to characterize the profile of older people with poor sleep quality and analyze possible associations with excessive daytime somnolence, quality of life and functional mobility.MethodsThis is a cross-sectional descriptive study, involving elderlies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(49 reference statements)
0
6
0
4
Order By: Relevance
“…Balance confidence contributes to functional mobility performance [ 39 ], and there seems to be a strong link between balance self-efficacy and function capabilities [ 51 ]. A study by Brandão et al [ 52 ] identified an association between excessive daytime sleepiness and quality of life, and also characterized the profile of older adults with poor sleep quality. Sleep duration is associated with inflammation markers (serum interleukin-6, tumor necrosis factor α, and C-reactive protein) in older adults, and in turn with mortality [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Balance confidence contributes to functional mobility performance [ 39 ], and there seems to be a strong link between balance self-efficacy and function capabilities [ 51 ]. A study by Brandão et al [ 52 ] identified an association between excessive daytime sleepiness and quality of life, and also characterized the profile of older adults with poor sleep quality. Sleep duration is associated with inflammation markers (serum interleukin-6, tumor necrosis factor α, and C-reactive protein) in older adults, and in turn with mortality [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Brandão et al [43], in a group of 131 elderly, the average ESS point value was 8.6 ± 2.8. In another study by Brandão et al [44], 40 seniors (30.5%) reported excessive daytime sleepiness as measured by the ESS, while the average ESS score in the study group was 8.32 ± 2.2 points, which is not an indication of excessive daytime sleepiness, similar to other studies [45, 46]. In the study of Tsuno et al [47], which included a population of 2184 elderly people in France, men more often scored > 10 points on the ESS compared with women – 12.0% men and 6.0% of women had excessive daytime sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…Yaşlılarda yaşam kalitesinin günlük yaşamda aktivite düzeyi, sağlıklı yaşam tarzı davranışları gibi değişkenler ile ilişkili olduğu gösterilmiştir (10,11). Ancak literatürde, yaşlı bireylerde uyku kalitesi ile yaşam kalitesi arasındaki ilişkinin incelendiği sınırlı sayıda çalışma mevcuttur (12).…”
Section: Bulgularunclassified